ADVANCED MRI PROTOCOL IN EVALUATION AND ASSESSMENT OF BRAIN TUMOR (International Journal of Food and Nutritional Sciences, 2022)
Background: Intracranial tumors are a significant health issue. The annual incidence of primary and secondary central nervous system neoplasms ranges from 10 to 17 per 100,000 persons.Imaging plays an important role in the management and prognostication of intracranial tumors. Magnetic resonance (MR) imaging has emerged as the imaging modality most frequently used to evaluate intracranial tumors, and it continues to have an ever-expanding, multifaceted role.Purpose:To evaluate the Advance brain tumor imaging (MRI) Protocol in Grading brain tumors both intra-axial and extra-axial.Methodology:This prospective study was performed. The population enrolled in the study for final statistical analysis included 40 patients (23 males and 17 females) with ages ranging from 3 to 79 years.Results:In the study, 37 (92.5%) patients showed supratentorial tumor location, and 3 (7.5%) patients showed infratentorial tumor location. On T1-W, 31 (77.5%) patients show a heterogeneously hypointense signal, 6 (15%) patients show an isointense signal, and 3 (7.5%) patients show a hypointense signal. On T2W, 37 (92.5%) patients show a heterogeneously hyperintense signal, and 3 (7.5%) patients show a hyperintense signal. On FLAIR, 37 (97.5%) patients show a heterogeneously hyperintense signal, and 1 (2.5% of patients) show a hyperintense signal. In the study, 28 (70%) patients showed no diffusion restriction, and 12 (30%) patients showed patchy diffusion restriction. On SWI 9, 22.5 percent of patients have "blooming," and 31 (77.5 percent) have "no blooming," indicating hemorrhage, which is seen in high-grade gliomas. In the post-contrast enhancement study, 17 (42.5%) patients showed patchy enhancement, 8 (20%) patients showed minimal enhancement, 5 (12.5%) patients showed heterogenous enhancement, and 10 (25%) patients showed no enhancement. In the study, there is no significant difference in the mean of age over the grade of a tumor by applying a two-sample t-test, in which the mean age for high-grade gliomas is 49.8 ± 19.8 and for low-grade gliomas is 38.83 ± 15.81, and we found no significant difference (P = 0.05928) in the distribution of grades of tumor in our study.